Localisation of a Global Brand Campaign : Case Study of Durex “Real Feel” - Bestová, Dominika; Průša, Přemysl, 1980-; Bahles, Michael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This bachelor thesis introduces in the beginning the basic theory of marketing and brands. The main topic there is the debate of standartization against local adaptation of marketing activities in the environment of global markets. The practical part then presents a case study of Durex brand, where a centrally developed campaign Real Feel was localized for needs of the United Arabic Emirates market.
Vedoucí práce: Přemysl Průša
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses